Persepsi Mahasiswa Akuntansi Tingkat Sarjana Terkait Audit Syariah (Studi Kasus Universitas Andalas) - Metria Susanti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Andalas, 2024)
This research aims to describe perception of undergraduate accounting students regarding sharia audit in West Sumatera. This research used a qualitative approach. The data wrere collected using survey questionnaires distributed to over 100 accounting students at Universitas Andalas. The results of this research indicated that the undergraduate accounting students at Andalas University have a fairly high level of awareness and knowledge about sharia audit. However, they do not understand further regarding the differences between sharia audits and conventional audits. The result of this research may be useful for those in charge of curriculum design.